The value of x for the given expression is;
x = -5/9
We are given the expression;
2x(x + 3) = (x + 1)(2x - 5)
Let us expand the brackets to get;
2x² + 6x = 2x² + 2x - 5x - 5
2x² + 6x = 2x² - 3x - 5
From this, 2x² is common to both sides and will cancel out to give;
6x = -3x - 5
Using addition property of equality to add 3z to both sides to get;
6x + 3x = -3x - 5 + 3x
9x = -5
Use division property of equality to divide both sides by 9 to get;
x = -5/9
Read more about algebra expressions at; https://brainly.com/question/4344214